IMPLEMENTASI KEBIJAKAN PENANGANAN LINGKUNGAN KUMUH DI KAWASAN BESUSU BARAT KECAMATAN PALU TIMUR - Lataha, Asfiani; Hattab, Syahrudin; Tjaiya, Abu (Katalogis, 2018)
This study aims to analyze the implementation of urban slum handling policies in the West Besusu Region, Palu Timur District, Palu City. The main theory that became the reference in this study was the theory of policy implementation by Edward III who saw the implementation of the policy by looking at 4 aspects, namely; (1) Communication Aspects, (2) Resource Aspects, (3) Disposition Aspects and (4) Aspects of the Bureaucratic Structure. The research method uses a descriptive-qualitative approach. The location of this study was located in West Besusu Village, East Palu District with informants as many as 5 people who were selected purposively. Data collection is done using Interactive models of Miles and Huberman. Based on the results of the study, the implementation of the policy of handling slum environments in the West Besusu area of East Palu District has not been running optimally. This can be seen based on the theory of Edward III in looking at the implementation of policies from 4 aspects, namely: aspects of communication, aspects of resources, aspects of disposition and aspects of bureaucracy, there are 2 aspects that still need to be improved and improved, namely aspects of communication which need to improve the form of communication the community can evenly understand the policy of handling slum environments in the West Besusu area of East Palu District and the aspects of facilities and infrastructure resources and budgets that have not been optimal so that it hampers the implementation of policies for handling slums in the West Besusu area of East Palu District.